Kaolinite deposition from moving suspensions: The roles of flocculation, salinity, suspended sediment concentration and flow velocity/bed shear. Issue 1 (14th September 2022) - Schieber, Juergen; Li, Zhiyang; Yawar, Zalmai; Cao, Xiaomeng; Ashley, Thomas; Wilson, Ryan
ABSTRACT: Understanding how mud moves and deposits is essential for conceptualizing the dynamic nature of surface environments and their ancient counterparts. Experimental study has largely been pursued by civil engineers, using kaolinite as an active ingredient. Yet, applying their data to the physical comprehension of mudstone sedimentology is hampered by multiple flume configurations between labs, and data sets tailored to specific engineering needs. The need for a better grasp of underlying processes is acute, given recent flume studies that show that moving suspensions form large bedload floccules, migrating floccule ripples and bed accretion under currents capable of moving sand grains. To advance mudstone sedimentology, integrated study of suspended sediment concentration, salinity and bed shear stress on the deposition of floccules is crucial. Described here is a set of tightly controlled experiments that explored suspended sediment concentrations from 70 to 900 mg/l, freshwater, brackish and marine salinities, flow velocities in the 5 to 50 cm/s range (equivalent to 0.01 to 0.58 Pa bed shear), measured the size of in‐flow and bedload floccules, and the critical velocity of sedimentation that marks the onset of sustained bedload accumulation. The critical velocity of sedimentation of kaolinite clays is in the 26 to 28 cm/s flow velocity range (0.22 to 0.25 Pa), appears insensitive to a wide range of suspended sediment concentrations and salinities, and coincides with the formation of sand‐size bedload floccules. Further decrease of flow velocity/bed shear stress is accompanied by a steady increase in the size of bedload floccules. Large bedload floccules appear to form in the high‐shear basal part of the flow, a phenomenon requiring further investigation. Better understanding of the mechanisms that facilitate mud deposition from moving suspensions is critical for more realistic assessments of the depositional conditions of mud and mudstones, as well as for refining predictive models for the flux of fine‐grained sediments across the Earth's surface.